Effect of combined microwave-ultrasonic pretreatment on anaerobic biodegradability of primary, excess activated and mixed sludge - Yeneneh, Anteneh; Sen, Tushar; Chong, Siewhui; Ang, Ha Ming; Kayaalp, A. (Scientific Research Publishing, Inc., 2013)
This work deals with the effect of combined microwave-ultrasonic pretreatment on the anaerobic biodegradability of primary, excess activated and mixed sludge. The characteristics, biodegradability and anaerobic digester performance for untreated primary, excess activated and mixed sludge were compared to combined microwave-ultrasonic pretreated primary, excess activated and mixed sludge. All sludge samples were subjected to Microwave treatment at 2450 MHz, 800 W and 3 min followed by ultrasonic treatment at a density of 0.4 W/mL, amplitude of 90%, Intensity of 150 W, pulse of 55/5 for 6min. Methane production in pretreated primary sludge was significantly greater (11.9 ml/g TCOD) than the methane yield of the untreated primary sludge (7.9 ml/g TCOD). Cumulative methane production of pretreated Excess Activated Sludge (EAS) was higher (66.5 ml/g TCOD) than the methane yield from pretreated mixed sludge (44.1 ml/g TCOD). Furthermore, digested EAS showed significantly higher dewaterability (201 s) than digested primary sludge (305 s) or mixed sludge (522 s). The average Methane: Carbondioxide ratio from EAS (1.85) was higher than that for mixed untreated sludge (1.24). VS reduction was also higher for EAS than the other two sludge types. However, pretreatment of EAS resulted in significant reduction in dewaterability due to higher percentage of fine floc particles in the pretreated EAS.